2014
DOI: 10.1016/j.taap.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of acetaminophen-induced cell death in primary human hepatocytes

Abstract: Acetaminophen (APAP) overdose is the most prevalent cause of drug-induced liver injury in western countries. Numerous studies have been conducted to investigate the mechanisms of injury after APAP overdose in various animal models; however, the importance of these mechanisms for humans remains unclear. Here we investigated APAP hepatotoxicity using freshly isolated primary human hepatocytes (PHH) from either donor livers or liver resections. PHH were exposed to 5mM, 10mM or 20mM APAP over a period of 48 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
213
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 215 publications
(229 citation statements)
references
References 39 publications
15
213
0
1
Order By: Relevance
“…Cells were isolated using a multi-step collagenase procedure as described in detail previously. 36 Media consisted of Williams' Medium E (Life Technologies, Grand Island, NY, USA) supplemented with L-glutamine (2 mM) (Life Technologies), HEPES (10 mM), insulin (10 āˆ’ 7 M), dexamethasone (10 āˆ’ 7 M), penicillin (100 U/ml), streptomycin (100 Ī¼g/ml) and amphotericin B (0.25 Ī¼g/ml). The hepatocytes were brought to a concentration of 0.5 Ɨ 10 6 cells/ml in Williams' Medium E, as described above, plus 5% bovine calf serum.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were isolated using a multi-step collagenase procedure as described in detail previously. 36 Media consisted of Williams' Medium E (Life Technologies, Grand Island, NY, USA) supplemented with L-glutamine (2 mM) (Life Technologies), HEPES (10 mM), insulin (10 āˆ’ 7 M), dexamethasone (10 āˆ’ 7 M), penicillin (100 U/ml), streptomycin (100 Ī¼g/ml) and amphotericin B (0.25 Ī¼g/ml). The hepatocytes were brought to a concentration of 0.5 Ɨ 10 6 cells/ml in Williams' Medium E, as described above, plus 5% bovine calf serum.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, primary human hepatocytes are difficult to attain, expensive, and of very limited supply. While some newer cell lines, such as HepaRG cells recapitulate more of the facets of primary human hepatocytes (4,(21)(22)(23), they still only express a relatively small degree of hepatocyte functional genes such as drug metabolizing enzymes and xenobiotic transporters (24). Human ESCs are highly proliferative, have an indefinite life span, and could thus be used to generate on a routine basis new and useful human hepatocyte-like cells that fairly accurately resemble primary human hepatocytes.…”
Section: Drug-induced Liver Injury-new Models New Methodsmentioning
confidence: 99%
“…Critical to the generation of new drugs is the continued development of our understanding of APAP-induced ALF in human patients. While a number of recent papers from our group and others have made considerable advances in understanding mechanisms of toxicity in patients and human hepatocytes (2)(3)(4)(5), there is still a lack of actionable therapeutic targets. Liver transplantation is the gold standard procedure for treating late-stage ALF but this operation is expensive and comes with additional costs of lifelong anti-rejection medication.…”
Section: Acetaminophen-induced Injury and Acute Liver Failure As A CLmentioning
confidence: 99%
“…This indicates that acylcarnitine levels in plasma may indeed reflect mitochondrial dysfunction, not cell death. Interestingly, acylcarnitine levels did not significantly increase during APAP hepatotoxicity in patients despite the evidence that mitochondrial dysfunction is critical for APAP-induced liver injury in patients [164, 268]. However, it was shown that treatment of mice with NAC, which does not only support GSH synthesis but also mitochondrial energetics [18], strongly reduced the increase in acylcarnitine levels in mice [266].…”
Section: Mitochondrial Biomarkers In Drug-induced Liver Injurymentioning
confidence: 99%